New product development management issues and decision-making approaches - Yahaya, Shahrul Yazid; Abu Bakar, Nooh (Emerald Group Publishing Limited, 2007)
Purpose - The purpose of this paper is to report findings related to new product development (NPD) management issues and their corresponding decision-making approaches undertaken by senior managers. Design/methodology/approach - The study adopts grounded theory research method using interview as the primary data source. 100 NPD management issues, sourced from 16 senior managers from six technology-based organizations in Malaysia, were investigated and analyzed. Findings - The study revealed four categories of NPD management issues; strategic NPD management issues, NPD project management issues, NPD process and structural issues, and NPD people management issues. The study also found that senior managers apply different patterns of decision-making approaches in dealing with each category of NPD management issues. Research limitations/implications - Although the findings from this study are within the specific context of technology-based organizations in Malaysia, this exploratory study opens up a number of questions for further investigation. Practical implications - The discussion from this paper should also stimulate senior managers from other organizations or from other locations to reexamine categories of management issues in their organizations and how they approach them from a decision-making perspective. This reflection could help identify areas which need further decision-making skills development. Originality/value - The classification of NPD management issues provides description of NPD management issues and the corresponding common decision-making approaches. The study which was carried out at technology-based organizations in Malaysia contributed to narrow down the geographical imbalances of NPD literatures, contributed to the body of NPD management literatures by bridging it with decision-making theoretical perspective, and contributed to the naturalistic decision research stream.